Cerebrovascular Imaging: Which Test is Best?. Issue 1 (23rd June 2017) - Lin, Amy; Rawal, Sapna; Agid, Ronit; Mandell, Daniel M
Abstract: Optimal diagnosis and characterization of cerebrovascular disease requires selection of the appropriate imaging exam for each clinical situation. In this review, we focus on intracranial arterial disease and discuss the techniques in current clinical use for imaging the blood vessel lumen and blood vessel wall, and for mapping cerebral hemodynamic impairment at the tissue level. We then discuss specific strategies for imaging intracranial aneurysms, arteriovenous malformations, dural arterial venous fistulas, and arterial steno-occlusive disease.